Sequential linear programming and particle swarm optimization for the optimization of energy districts. Issue 1 (2nd January 2019) - Riccietti, Elisa; Bellavia, Stefania; Sello, Stefano
Abstract: This article deals with the optimization of energy resource management of industrial districts, with the aim of minimizing customer energy expenses. A model of the district is employed, whose optimization gives rise to a nonlinear constrained optimization problem. Here the focus is on its numerical solution. Two different methods are considered: a sequential linear programming method and a particle swarm optimization method. Efficient implementations of both approaches are devised and the results of the tests performed on several energetic districts are reported, including a real case study.